Analisis Faktor-Faktor Yang Mempengaruhi Keputusan Kuliah Di Perguruan Tinggi Swasta - masduki ir; Endah Prihartini; Dudung Abdullah (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2023)
The community's decision in choosing a university is an activity that requires a lot ofconsideration. Basically, the decision to choose a university is always related to the marketingprocess by the party offering the service. This is in line with the opinion of Mulyawan andSidharta (2013) in Shaleh et al., (2018) which states that service marketing plays animportant role in meeting consumer needs, including the need for input in choosinguniversities. The purpose of the study was to determine the contribution of motivation,attitudes, personality (internal factors), reference groups, family, college image, andpromotion via social media (external factors) to the decision to study in private universities.The data analysis technique used Structural Equation Modeling (SEM) with the help of AMOS21 software. The population in this study was Majalengka University students with a sampleof 198 people, and the sampling technique used was proportionate random sampling. Theresults of the research show that partially motivation, personality, family support, collegeimage, and promotion via social media have a significant contribution to the decision to studyin private universities. Meanwhile attitudes and reference groups did not significantlycontribute to the decision to study in private universities. The two most dominant factors incontributing to college decisions are family support and college image.